Expression of Microsomal Prostaglandin E Synthase-1 in the Spinal Cord in a Transgenic Mouse Model of Amyotrophic Lateral Sclerosis - Hiroko Miyagishi; Yasuhiro Kosuge; Kumiko Ishige; Yoshihisa Ito (Elsevier, 2012)
Prostaglandin E2 (PGE2) is a key molecule involved in the neuroinflammatory processes that characterize amyotrophic lateral sclerosis (ALS). Although PGE2 synthesis is regulated by PGE2 synthases (PGESs), the pathological role of PGESs in ALS still remains unknown. Experiments were performed to elucidate the expression of PGESs and the localization of microsomal PGES-1 (mPGES-1) in neurons and glial cells in the spinal cord of ALS model (G93A) mice. Neurological symptom was observed in G93A mice from 14 weeks by the tail suspension test, and rotarod performances were decreased at 16 weeks and older. Western blotting revealed that the level of mPGES-1 was increased in G93A mice at 15 weeks and older. In contrast, the levels of cytosolic PGES and mPGES-2 did not change at any age. Immunohistochemical analysis demonstrated that age-dependent expression of mPGES-1 was found in motor neurons in G93A mice at 11 and 15 weeks. Immunoreactivity of mPGES-1 was also co-localized in Iba1-positive microglia in G93A mice at 15 weeks. These results suggest that mPGES-1 in motor neurons may play a role in the pathogenesis of ALS and that mPGES-1 may work sequentially in motor neurons and activated microglia to produce ALS symptoms in G93A mice. Keywords:: amyotrophic lateral sclerosis, motor neuron, microglia, prostaglandin E2, microsomal prostaglandin E synthase-1